(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This work defends the strength of the contextual and combinatorial arguments of the hypothesis proposed by Eduardo Orduña about the identification of several Iberian elements as numerals. Addition- ally, some aspects of the original hypothesis are corrected and new positive arguments are added, the most relevant are those related to the marks of value of the Iberian coins, because they are compatible with some of the proposed numerals.